Natural silk fiber microcarriers for cell culture - M. M. Bobrova; L. A. Safonova; A. E. Efimov; O. I. Agapova; I. I. Agapov (Вестник трансплантологии и искусственных органов, 2021)
The development of effective and versatile microcarriers is a pressing issue in tissue engineering and regenerative medicine. The objective of this work is to create biocompatible fiber microparticles from the cocoons of the Bombyx  mori silkworm, and to study their structure and biological properties. Materials and methods. In obtaining microparticles, the Bombyx mori cocoons washed from sericin were cryo-milled in liquid nitrogen. The structure of the resulting microparticles was analyzed via scanning electron microscopy. The cytotoxicity of the obtained fibers was assessed using MTT-cell culture assay of 3T3 mouse fibroblasts. Cell adhesion analysis was performed using the Hep-G2 human hepatocarcinoma cell line. Cell visualization was performed by staining the nuclei with DAPI fluorescent dye. Results. Natural silk microparticles were obtained in the form of cylindrical fibers with 200–400 μm average length and 15 μm diameter. It was shown that the surface of the resulting microparticles has a rough relief; no pores were found. The microparticles are non-toxic for 3T3 mouse fibroblasts, they maintain a high level of adhesion by human hepatocellular carcinoma HepG2 cells. Conclusion. The method developed by us for fabrication of biocompatible silk fibroin microparticles in the form of fibers without using toxic reagents and significant time costs is promising for cell cultivation and delivery to the damaged area for tissue and organ regeneration.